Epidemiology and Management of Atrial Fibrillation and Stroke: Review of Data from Four European Countries - Andreea D. Ceornodolea; Roland Bal; Johan L. Severens (Stroke Research and Treatment)
In Europe, 1–3% of the population suffers from atrial fibrillation (AF) and has increased stroke risk. By 2060 a doubling in number of cases and great burden in managing this medical condition are expected. This paper offers an overview of data on epidemiology and management of AF and stroke in four European countries as well as the interconnection between these dimensions. A search index was developed to access multiple scientific and “grey” literatures. Information was prioritised based on strength of evidence and date. Information on country reports was double-checked with national experts. The overall prevalence of AF is consistent across countries. France has the lowest stroke incidence and mortality, followed by Netherland and UK, while Romania has higher rates. GPs or medical specialists are responsible for AF treatment; exception are the special thrombosis services in the Netherlands. Prevention measurements are only present in UK through screening programs. Although international and national guidelines are available, undertreatment is present in all countries. Despite differences in healthcare systems and management of AF, epidemiology is comparable between three of the countries. Romania is an outlier, by being limited in data accessibility. This knowledge can contribute to improved AF care in Europe.